PanromanIC. Manuale di intercomprensione fra lingue romanze. Susana Benavente, F., Calvo del Olmo, F., Hilde Frisan, E., Manole, V., Marielly Rocha da Cunha, K. & Sheeren, H. (Eds.) (2022). Bologna: Zanichelli - Llamedo Pandiella, Gonzalo (Lletres Asturianes, 2024)
-